Hubungan Usia Ibu, Pekerjaan Ibu dan Pendapatan Keluarga dengan Waktu Pertama Pemberian MP-ASI di Posyandu Kelurahan Bugel Kota Salatiga - Pramita, Adiene; Sumarmi, Sri (Media Gizi Kesmas, 2024)
Background: Complementary feeding at six months old has an important role in the nutritional adequacy infants. Complementary feeding last than six months and more than six months had the same risk for lack of nutrition cases. Characteristics of mothers like mother’s age, mother’s work status, and family income can influence the first time complementary feeding. Objectives: This study aims to analyzed correlations between mother’s age, mother’s work  status, and family income with first time complementary feeding. Methods: This research was an observational with cross-sectional method. Population of the study was 176 toddlers with total sample 69 toddlers and their mother became the respondents. The instrument that used in this research were interview and questionnaire. For knowing the correlation, this research using Chi-Square test. Results: Based on the results of the study, most of the respondents were in the adult age group (26-45 years) as many as 63 respondents (91.3%), the non-working group were 57 respondents (82.6%), and the income group was IDR 2,000,001 – IDR 4,200,000 as many as 36 respondents (52.1%). From the results of  Chi-Square test, there was negative correlations between mother’s age (p=0.571) and family income (p=0.672) with first time complementary feeding but positive correlations between mother’s work status with first time complementary feeding (p=0.001). Conclusions: There were no correlations between mother’s age and family income with first time complementary feeding. There was a correlation between mother’s work status with first time complementary feeding. However the more time mother could spent, the more first-time complementary feeding would exact time.